Efficacy and safety of anakinra and canakinumab in PSTPIP1-associated inflammatory diseases: a comprehensive scoping review - Sanz-Cabanillas, Juan Luis; Gómez-García, Francisco; Gómez-Arias, Pedro Jesús; Montilla-López, Ana; Gay-Mimbrera, Jesús; Ruano, Juan; Isla-Tejera, Beatriz; Parra-Peralbo, Esmeralda (Frontiers in Immunology, 2024)
Introduction: This scoping review explores the effectiveness of IL-1 pathway inhibitors in managing PSTPIP1-associated inflammatory diseases (PAID). These diseases are marked by abnormal IL-1 pathway activation due to genetic mutations.Our methodology adhered to a pre-published protocol and involved a thorough search of MEDLINE and EMBASE databases up to February 2022, following the Joanna Briggs Institute Reviewer's Manual and the PRISMA Extension for Scoping Reviews.The review included studies reporting on IL-1 pathway inhibitor use in PAID patients.Results: From an initial pool of 5,225 articles, 36 studies involving 43 patients were selected. The studies predominantly used observational designs and exhibited diversity in patient demographics, treatment approaches, and outcomes. Anakinra and canakinumab demonstrated promise in treating sterile pyogenic arthritis, pyoderma gangrenosum, and acne (PAPA) and PSTPIP1-associated myeloid-related-proteinemia inflammatory (PAMI) syndromes, with scant data on other syndromes. Notably, there was a paucity of information on the adverse effects of these treatments, necessitating cautious interpretation of their safety profile.Conclusions: Current evidence on IL-1 pathway inhibitors for PAID is primarily from observational studies and remains limited. Rigorous research with larger patient cohorts is imperative for more definitive conclusions. Collaborative efforts among specialized research centers and international health initiatives are key to advancing this field.